1975
DOI: 10.1128/jvi.16.2.453-455.1975
|View full text |Cite|
|
Sign up to set email alerts
|

Biological functions of the bacteriophage T3 SAMase gene

Abstract: Certain differences between phage T3 on the one hand and T3sam and T7 on the other hand indicate that the T3-coded SAMase function is responsible (i) for the development of the pseudolysogenic state by preventing T3 DNA methylation, and (ii) for the partial protection of the phage DNA against restriction by the P system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…To further evaluate the requirement of SAM as a cofactor of viperin, we reduced the intracellular SAM levels by means of a SAM-cleaving enzyme, SAMase (also called S-adenosyl-L-methionine hydrolase or AdoMetase). The cDNA sequence of the Escherichia coli bacteriophage T3 (Hausmann, 1967;Krueger et al, 1975; C. Immunoblot analysis of cells transfected with FLAG-ΔMx, FLAG-viperin and SAMase using antisera specific for the FLAG epitope (staining FLAG-tagged ΔMx and viperin), or actin. Hughes et al, 1987) was chemically synthesized and cloned into the eukaryotic expression vector pI.18 (see Experimental procedures).…”
Section: Antiviral Action Of Viperin Is Based On the Radical Sam Domamentioning
confidence: 99%
“…To further evaluate the requirement of SAM as a cofactor of viperin, we reduced the intracellular SAM levels by means of a SAM-cleaving enzyme, SAMase (also called S-adenosyl-L-methionine hydrolase or AdoMetase). The cDNA sequence of the Escherichia coli bacteriophage T3 (Hausmann, 1967;Krueger et al, 1975; C. Immunoblot analysis of cells transfected with FLAG-ΔMx, FLAG-viperin and SAMase using antisera specific for the FLAG epitope (staining FLAG-tagged ΔMx and viperin), or actin. Hughes et al, 1987) was chemically synthesized and cloned into the eukaryotic expression vector pI.18 (see Experimental procedures).…”
Section: Antiviral Action Of Viperin Is Based On the Radical Sam Domamentioning
confidence: 99%
“…It is possible that bacteriophage T7 and the T3 SAMmutants only partially inhibit, or alter the specificity of, the methylation enzymes of the host cell. Krueger et al (13) have found that in poorly growing cells, T3 SAMand T7 both give rapid, productive responses, whereas T3 SAM' phage particles are only slowly expressed. In mixed infections of T3 SAMand T3 SAM' or T7 and T3 SAM', the virus types having no SAMase activity (and, presumably, methylated DNA) are dominant, yielding rapid lysis and a high burst size.…”
mentioning
confidence: 99%
“…SAMase (GOLD et al. 1964, HAUSMA" 1967, KRUGER et al 1975, 1977c, STUDIER and MOWA 1976. Previously "non-classical" modification and restriction of phages has within 3 months and is down to although these strains differ significantly in their ability to modify T3.…”
Section: Resultsmentioning
confidence: 99%